Perancangan Struktur Apartemen 15 Lantai Dengan Menggunakan Beton Bertulang di Jl.Jendral Ahmad Yani, Kota Pontianak,Kalimantan Barat - Justitiannisa, Innino Nino (Jurusan Teknik Sipil Polnep, 2021)
The increasing need for housing from year to year is increasing. The increase in population is the main factor and the availability of land is not supported. Based on the Pontianak City Spatial Plan 2013 - 2033, the land requirement for housing reaches 4580.31 hectares. Vertical development, namely apartments, aims to save land use and still be able to meet large numbers of residential needs. This apartment planning uses standards according to SNI 03-2847-2002 with the use of SAP 2000 software program. Site plan design, drawing desing and structural calculations in designing this apartement. This apartement design aims to produce apartement structures with reinforced concrete that are sturdy, safe, amda economical. Planning for this apartment starts from site plan planning, drawing design, spatial planning, floor slabs, internal forces, and foundation. In the preparation of this final project, quantitative methods are used, and primary and secondary data collection. The specifications for the construction of the apartment use reinforced concrete, using pile foundations, dak roofs, fc '30, and fy 400. 12 cm; 2 types of main beam and beam size, each measuring 55 cm x 45 cm, 50 cm x 40 cm, 45 cm x 35 cm, and 35 cm x 30 cm; 3 types of sizes, respectively 65 cm x 65 cm, 60 cm x 60 cm, and 50 cm x 50 cm; and 3 types of foundation with different number of piles, namely 9, 12, 20, and 24 pile points.